Effect of Palmito cheese processing on sensory characteristics and degree of liking - Marín-Fonseca, Andrea (2023)
Introduction. The production of regional food with local and cultural identity has become an attractive business for small-scale producers because it allows them to market their products highlighting local ingredients and traditional processing that reflects the know-how of each region. One example is Pasta filata cheese. Objective. To identify sensory characteristics and level of liking for Costa Rican Pasta filata cheeses (Palmito cheese). Materials and methods. The project was carried out at the facilities of the University of Costa Rica, during 2015. Nineteen samples of Costa Rican Palmito cheese were used, with fourteen of them being produced by artisanal producers and five by industrial producers. The methodology of Generic Quantitative Descriptive Analysis (QDA) was followed, with ten trained judges defining twenty-one attributes. Agglomerative Hierarchical Clustering (AHC) and Principal Component Analysis (PCA) were conducted to relate the samples to their attributes. Acceptance testing was performed with one hundred consumers. Consumer AHC and external preference mapping were applied to correlate the results of the liking with those of the QDA. Results. Significant differences (p<0,05) among samples were obtained in the QDA for all attributes. The samples were grouped into three clusters based on similarity attributes. The PCA showed one group, primarily consisting of traditional cheeses, clustered by attributes such as acid and salty flavor, firmness, moisture, and stringy appearance. Another group, corresponding to refrigerated, pasteurized, and unpasteurized cheeses, had a higher intensity of yellow color, greasy texture, softness, and less stringy appearance. A final group, composed of one sample, had a lettuce flavor. Conclusion. Through the external preference mapping, it was concluded that consumers like the majority of industrial Palmito cheeses, but they prefer traditional ones with characteristics such as stringy and creamy flavor.